The Reconstruction of the Cultural Worldview of Islam in the Face of Modern Jahiliyah: An Examination of the Study of Maʿālim Fī Al-Ṭarīq by Sayyid Quṭb - Riyadi, Muhamnad Irfan; Hambali, Ridwan Hambali (Qurthuba: The Journal of History and Islamic Civilization, 2026)
Abstract: This study aims to analyze the concept of modern Jāhilīyah and the negotiation pattern of Islamic culture in Sayyid Qutb's Maʿālim fī al-Ṭarīq. Departing from the problem of modernity that gave rise to identity crises, secularization, materialism, and moral degradation in Muslim society, Qutb reconceptualized Jāhilīyah not as a pre-Islamic period, but as a social condition characterized by a rejection of Allah's ḥākimiyyah and the dominance of secular values. This research uses a literature approach with content and descriptive-qualitative methods, and is framed with the theories of cultural negotiation by John W. Berry, Kevin Avruch, and Stella Ting-Toomey. The results of the study show that Qutb proposed a pattern of total resistance (separation) through the concept of mufāṣalah and the formation of the Islām generation (takwīn al-jīl) as a counter culture to modern Jāhilīyah. In the context of a plural and democratic Indonesia, his thinking is relevant as a critique of secularism and materialism, but it needs to be read contextually and moderately so as not to give birth to religious exclusivism. Keywords: Cultural Negotiation, Islamic Culture, Modern Jāhilīyah, Sayyid Quṭb